Determining Factors for the Early Termination of the Career of Soccer Players - Luís Felipe De Matos Borges; Luciano Bernardes Leite; Leonardo Mateus Teixeira Rezende; Lucas Rogério dos Reis Caldas (Universidade Salgado de Oliveira, 2022)
The aim of the present study was to analyze the factors with the greatest influence on the early termination of the career of soccer players. The sample consisted of 40 former professional soccer athletes. To collect the results, a semi-structured questionnaire was used, elaborated by the authors themselves, which addressed topics such as athletes' biography; psychological and sociological aspects of the career; causes, problems, and difficulties with the end of a career; emotions experienced in this process and the occurrence of injuries throughout the career. Data were analyzed quantitatively through the distribution of absolute and relative frequency. By analyzing the results, it was possible to verify that 55% of the sample abandoned their football player career in the age group of 21 to 25 years. In addition, 37.5% of the sample received an amount equivalent to less than the minimum wage when they were still football players. In relation to the current monthly income, 52.5% of the sample currently receives between 1 to 2 minimum wages. It was also possible to observe that 90.0% of the sample chose the profession of soccer player because of "Pleasure in playing soccer". On the other hand, the main reason for abandoning the football player career was the "Lack of stability in the profession" with a percentage of 37.5%. The results of the present study showed that the lack of stability and low salaries in the football player profession, in addition to injuries throughout their careers, were the main reasons for early abandonment of the profession.